Alternative Ways of Overcoming a Region's Spatial Discontinuity - Eleni Gaki; Vasilis Angelis; Katerina Dimaki (European Regional Science Association (ERSA), 2010)
The development of regions and especially those facing spatial discontinuity has been the focus in some previous work (Angelis 1980, 1999) and the region's Image has been defined as a variable expressing its relative attractiveness and its prospects of future development. The findings have been applied to selected Greek regions and the results have been discussed. Among the factors affecting a region's Image, accessibility to markets, resources and influence centres, seems to be a very crucial one and its improvement will facilitate its development. Although several measures for improving a region's accessibility have been suggested, they seem to have little or no effect for regions with spatial discontinuity. In this case, alternative measures have been introduced and a modification of the initial region's Image concept has been proposed so as to take into account the variables related to those measures (Gaki, Angelis, Dimaki 2009). The use of the modified Image functions for regions with spatial discontinuity seems to be a step in the right direction since, on one hand, they give a better view of their current state of development and future prospects and, on the other hand, they may be used as the basis for the design, but also for the evaluation, of alternative specific measures aiming to assist them in overcoming their problem. One of the measures suggested for this purpose is the development of local business activities, i.e. activities basically using local resources and selling their products to local markets. For such activities discontinuity is not a handicap since their development doesn't require frequent transportation of physical entities to-and-from other regions. Our objective in this paper is to focus on this solution. Toward this end we: - Determine the characteristics that a region should have in order to implement such a solution - Redefine the Image function so as to include those characteristics - Apply the theoretical findings to selected Greek regions - Compare the findings with those obtained when the initial Image function was used and summarize the conclusions.
Keywords: 330; Region's Image; Regional Development; Spatial Discontinuity; Local Business Activities